Developments of Chilled Sweetened Gozo (Kappaphycus Alvarezii Doty) Salad in Two Different Types of Preparation Mixed with Diced Mango (Magnifera Indica Linn.) - Ronald M. Ramirez (International Journal of Advanced Science and Technology, 2018)
The study was conducted in order to find out whether gozo (Kappaphycus alvarizzi) could be a good ingredient for salad preparation with diced mango. Experimental method was used in the study. There were two processes used in the preparation, soaking and boiling and there were six treatments for each method used. For soaking preparation, TOS was fruit salad using nata de coco, nestle cream and condensed milk, T1S was gozo soaked with boiled water for five (5) minutes in pan, T2S was gozo soaked with boiling water for (10) minutes, T3S was gozo soaked with boiling water for fifteen (15 minutes), T4S was gozo soaked with boiling water for twenty (20) minutes, T5S, gozo was soaked with boiling water for twenty five (25) minutes. For boiling preparation, (T0B was fruit salad) using nata de coco, nestle cream and condensed milk. T1B gozo was boiled with a continuous supply of fire for five (5) minutes in a kettle, T2B gozo was boiled with a continuous supply of fire for ten (10) minutes, T3B gozo was boiled for fifteen (15) minutes, T4B gozo was boiled for twenty (20) minutes, T5B gozo was boiled for twenty five (25) minutes in a kettle. All the treatments were mixed with ingredients similar to the fruit salad ingredients except that gozo was made to substitute nata de coco and diced mango. Results based on the color show that T2S for was like moderately and T5B was like moderately in boiling preparation. For odor, T4S was likely moderately in boiling. For flavor it was found out that T4S was like moderately (soaked) and T2B (boiled) was like moderately. For texture T1S (soaked) was like moderately and T5B (boiled) was like moderately. Results further revealed that there was no significant mean difference in all attributes between soaking and boiling as a method and time of preparation at 1% level of significance.